2019
DOI: 10.1089/trgh.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Protocol for Transmasculine Voice: A Service Evaluation of the Voice and Communication Therapy Group Program, Including Long-Term Follow-Up for Trans Men at the London Gender Identity Clinic

Abstract: Purpose: A service evaluation was undertaken with 10 participants identifying as trans men who received voice and communication group therapy and 12-month follow-up at the London Gender Identity Clinic between February 2017 and March 2018, to investigate levels of satisfaction, how helpful they found the program in facilitating vocal change and skill development, and whether they would recommend it to others. Methods: Participant evaluations of overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In this sense, one of the studies with an experiment conducted with transgender women points out that a therapy focused on oral resonance could improve the perception of listeners regarding the femininity of the voice [19]. In agreement with this point, another clinical experiment conducted with transgender men achieved fullbodied voice resulting from the combination of several exercises for resonance modification [15]. The authors of this article discuss and demonstrate that the reduction of fundamental frequency alone does not satisfy a complete gender identity, and interventions are also needed in vocal dynamics (pitch, resonance, loudness, intonation and vocal quality) and in social communication skills in order to achieve good results [15].…”
Section: Literature Reviewmentioning
confidence: 75%
See 4 more Smart Citations
“…In this sense, one of the studies with an experiment conducted with transgender women points out that a therapy focused on oral resonance could improve the perception of listeners regarding the femininity of the voice [19]. In agreement with this point, another clinical experiment conducted with transgender men achieved fullbodied voice resulting from the combination of several exercises for resonance modification [15]. The authors of this article discuss and demonstrate that the reduction of fundamental frequency alone does not satisfy a complete gender identity, and interventions are also needed in vocal dynamics (pitch, resonance, loudness, intonation and vocal quality) and in social communication skills in order to achieve good results [15].…”
Section: Literature Reviewmentioning
confidence: 75%
“…Of the nine texts analyzed, all addressed voice as a gender marker, anatomical differences between men and women [2,4,[13][14][15][16][17][18][19]. One of these studies13 confirmed that vocal and facial information is processed together to identify the person and gender as a whole, which reinforces the need for the transgender person to adapt the voice with the visually manifested gender to improve communication and the perception of gender authenticity.…”
Section: Literature Reviewmentioning
confidence: 94%
See 3 more Smart Citations